شـــعــريـــــة الـــوصـــف في روايـــــة قــــواريــــر شــــارع جــــميــلــــة بـــوحيــــرد لــلكاتبة ـربيــــعـــة جــــلطـــي - عمري، هاجر; غربي، سمية; لموشي، فاطمة (University of Eloued جامعة الوادي, 2025)
الملخص: تسعى هذه الدراسة إلى تجربة مغاير ومتألقة عن نظيراتها من ألوان التجريب في الرواية الجزائرية المعاصرة، فكانت دراسة رواية قوارير شارع جميلة بوحيرد للروائية ربيعة جلطي. حيث تمكنت الروائية من تحطيم البنية التقليدية للسرد فنجدها تعتمد على تقنية السرد المعاصر، وهذا ما يعكس وعيًا فنيًا متقدمًا، وأيضًا علاقة بين المرأة - قوارير – وبين رمزية شارع جميلة بوحيرد، وكذلك علاقة بين المعاناة الفردية والنضال الجماعي، فقد كانت هذه الرواية مفعمة بما يحيط بعوالم المرأة الجزائرية جسد واقع حياتها الاجتماعية والوجدانية والسياسية ليس كشخصية فقط، بل كصوت يملك سلطة التأويل والسرد وإطلاق الحكم على الأشياء. ثم تركت الرواية بصمة في مسار السرد النسوي الجزائري فتألق في أجمل حلة شعرية وصفية سردية في عالم الروائية الجزائرية. Résumé : فرنسية أو انجلزية This study aims to a distinctive and innovative experience compared to other forms of novelistic creativity in the contemporary Algerian novel, so is the novel " Kawarir " by the author Rabia Jaalti, which breaks the traditional structure of narration. The author depends on contemporary narration technique and that reflects an advanced artistic awareness. Moreover, the novel connects the suffering of women'' Kawarir '' and the symbolism of Djamel Bouhired Street which links the individual female sufferings with the collective struggle. This novel is rich with what surrounds the Algerian woman's worlds shaping her social, emotional, and political existence, not only as a personality but as a voice that has the authority to interpret, narrate, and judge things. Thus, the novel has left a significant imprint in the path of Algerian feminist narrative; hence, it has shone in the most beautiful poetic and descriptive narrative form within the world of the Algerian woman .
مذكرة ماستر. نقد حديث ومعاصر.2025
Keywords: شعرية الوصف في رواية قوارير شارع جميلة بوحيرد; Poetics of description in the novel Bottles of Djamila Bouhired Street